Formation of readiness for professional and creative activity of future architects in the process of teaching engineering graphics - Mysalimov, Темиржан; Baidabekov, Ауез (Рroblems of engineering and professional education, 2022)
In the article the author investigates the problems of readiniss ti the professional and creative activity students in the process of engineering graphics